Good Governance Dalam Konteks Hukum Administrasi - Sri Nur Hari Susanto (Administrative Law and Governance Journal, 2019)
Abstract The research aims to determine the practice of implementing good governance in the context of administrative law. This writing is a legal writing that uses a conceptual approach. The results of the study show that the legislative body in carrying out the regulatory function must base on good / decent regulatory principles / principles by developing knowledge and skills in the field of legislation as mandated by Law Number 12 Year 2011 along with its attachments. In general, there are two main means used to assess good / decent governance, namely Procedure and Facts used in making decisions, in addition to attention to several legal principles as a manifestation of the implementation of the principle of democracy. Judicial control in overseeing government actions against decisions made, including in Judicial Review, which are repressive and prioritize the legality aspect (rechtmatigheid) of a decision. Keyword: Good governance, Administrative law. Keywords: Good Governance, Administrative Law, government  Abstrak Penelitian bertujuan untuk mengetahui praktek pelaksanaan good goveranance dalam konteks hukum administrasi. Penulisan ini merupakan penulisan hukum yang menggunakan pendekatan konseptual. Hasil penelitian menunjukan bahwa Badan legislatif dalam menjalankan fungsi regulasi wajib mendasarkan pada prinsip-prinsip/ asas-asas regulasi yang baik/layak dengan mengembangkan pengetahuan dan ketrampilan di bidang perundang-undangan sebagaimana diamanatkan oleh Undang-Undang Nomor 12 Tahun 2011 beserta lampirannya. Pada umumnya terdapat dua sarana utama yang dipergunakan untuk menilai tentang penyelenggraaan pemerintahan yang baik/layak, yakni Prosedur dan Fakta yang dipergunakan dalam mengambil keputusan, di samping perhatian terhadap beberapa prinsip hukum sebagai wujud dari pelaksanaan asas demokrasi. Kontrol peradilan dalam mengawasi tindakan pemerintah terhadap keputusan yang dibuatnya, termasuk dalam Judicial Review,  yang bersifat represif dan mengutamakan aspek legalitas (rechtmatigheid) dari suatu keputusan. Keyword : Good governance, Administrative law. Kata Kunci: Good Governance, Hukum Administrasi, pemerintahan